Analysis of Electric Vehicle Charging Infrastructure Readiness in Urban Areas - Saputra, Fajar Rahman; Wicaksono, Nadya Putri; Yin, Hang (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The rapid growth of electric vehicle adoption has intensified the need for adequate charging infrastructure in urban areas. Infrastructure readiness determines accessibility, user confidence, and the pace of electrification in cities. This study analyzes the readiness of electric vehicle charging infrastructure in urban areas through a systematic literature-based analytical approach. The research synthesizes findings from international empirical studies, planning models, spatial analyses, and policy evaluations published between 2012 and 2025. The method applies structured content analysis to examine key dimensions of readiness, including spatial coverage, accessibility, technological configuration, policy support, and grid integration. The results show persistent spatial inequalities in charger distribution, mismatches between demand and supply, and limited integration between charging infrastructure and urban planning systems. Fast-charging deployment improves coverage efficiency but creates grid and cost challenges. Smart charging and data-driven planning models enhance readiness but remain underutilized in developing cities. The study concludes that urban charging readiness depends on coordinated planning, multi-criteria site selection, policy alignment, and grid-aware deployment strategies. These findings provide evidence-based guidance for policymakers and urban planners to accelerate sustainable electric mobility.